The Ideal Plasticity Theory Usage Peculiarities to Concrete and Reinforced Concrete - Pohribnyi, Volodymyr; Dovzhenko, Oksana; Maliovana, Olena (International Journal of Engineering and Technology, 2018)
The usage aspects of ideal plasticity theory for concrete and reinforced concrete are investigated. The plastic deformation is considered to be localized n thin layers on the failure plane which divides the element into rigid parts. The variation method is used and the solutions in discontinuous functions are received. The functional of virtual velocities principle is investigated to stationary condition, the minimal capability of plastic deformation is found with which the solid changes into the mechanism. The limit and realization criterion of concrete failure under shear are set. The reinforcement influence on the element load-carrying capacity is taken into account.Â